English lexical items in Egyptian Arabic. Code-switching or borrowing? - Kniaź, Małgorzata (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2017)
The study aims to answer the question of whether lone English items that occur in Arabic-English code-switching are borrowings or code-switches. This is based on empirical data collected at the American University in Cairo. The data were analyzed within the framework of the Matrix Language Frame model. 3443 bilingual projections of complementizer (CP) were investigated. They were divided into two types: (1) CPs with Arabic as the Matrix Language (ML) and (2) CPs with English as the ML. The analysis shows a clear discrepancy between categories of items used in the two types. In Arabic CPs, the most frequently switched category concerns English nouns related to the field of study and academic life as well as Standard Arabic in monolingual discourse. The interviews conducted with the participants in the study revealed that they were mostly used due to the lack of Arabic equivalents at the speakers’ disposal. In English CPs, mainly Arabic conjunctions and discourse markers appear. We claim that this categorial and functional variation between Arabic and English results from the linguistic situation in the Arab world. For bilingual speakers in Arabic diglossic communities, educated in schools with instruction in English and non-proficient in Standard Arabic, English items are the only means to communicate in many fields. Such items become part of their mental lexicon and thus should be considered as borrowings even if they are not established loans.